Biodegradable magnesium‐based biomaterials: An overview of challenges and opportunities. Issue 2 (8th April 2021) - Amukarimi, Shukufe; Mozafari, Masoud
Abstract: As promising biodegradable materials with nontoxic degradation products, magnesium (Mg) and its alloys have received more and more attention in the biomedical field very recently. Having excellent biocompatibility and unique mechanical properties, magnesium‐based alloys currently cover a broad range of applications in the biomedical field. The use of Mg‐based biomedical devices eliminates the need for biomaterial removal surgery after the healing process and reduces adverse effects induced by the implantation of permanent biomaterials. However, the high corrosion rate of Mg‐based implants leads to unexpected degradation, structural failure, hydrogen evolution, alkalization, and cytotoxicity. To overcome these limitations, alloying Mg with suitable alloying elements and surface treatment come highly recommended. In this area, open questions remain on the behavior of Mg‐based biomaterials in the human body and the effects of different factors that have resulted in these challenges. In addition to that, many techniques are yet to be verified to turn these challenges into opportunities. Accordingly, this article aims to review major challenges and opportunities for Mg‐based biomaterials to minimize the challenges for the development of novel biomaterials made of Mg and its alloys. Abstract : Magnesium (Mg)‐based alloys have shifted into the focus as a new generation of degradable biomaterials for medical applications. Because biodegradable Mg‐based alloys possess excellent biocompatibility and unique mechanical properties, deploying these biomaterials eliminates the need for biomaterial removal surgery after the healing process and diminishes adverse effects induced by implantation of permanent implants. This article reviews the main challenges following the implantation of Mg‐based biomaterials in the human body. It also introduces a broad overview of opportunities to minimize the challenges for the development of advanced biomaterials made from Mg and its alloys.